Influence of sGnRH-a + Domperidone With Different Doses for Ovulation Stimulation, Egg and Larvae Quality of The Pawas (Osteochilus hasselti CV) - Septiana Anggraini; Sukendi '; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted over 60 days, starting on April 20 until June 8 2015, at the Hatchery and Breeding Laboratory at Fisheries and Marine Science Faculty, University of Riau. This research aims to determine the effect of sGnRH-a + domperidone with different doses of the ovulation stimulation and the eggs quality of Nilem Carp (O. hasselti CV) which is the first step of research and then the best dosage obtained through observations in the first step will then be injected against gonads mature female brood and then will spawn with the male injected with the best dose (0.4 ml/kg body weight) through research